PEMILIHAN BAHAN PEMULIAAN PADI UNTUK PEMBENTUKAN VARIETAS UNGGUL DISKRIMINATIF TUMPANG SARI : PADI + JAGUNG + UBI KAYU DI LAHAN KERING II. STABILITAS RELATIF HASIL GABAH - Abdul Bari (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1997)
Intercropping of maize, rice, and cassava is commonly practice by subsistent farmer on rainfed agriculture in Indonesia. In general grain yield of rice in intercropping is lower than monoculture sole crop. This due to the fact that rice varieties planted in intercropping was bred and selected under elite, monoculture crop environment. Field experiments to evaluate grain yield relative stability of the three selected rice breeding materials planted in association with maize and cassava were carried out in Pekalongan (Lampung), December 1994 - September 1995. Tb153e-Tb-1 and Tb47h-Mr-17 are relatively stable in respect to grain yield. Individual mass selection in these two population will be practiced in association with maize and cassava.